BEHAVIOR OF POLYMER-MODIFIED BENTONITES WITH AGGRESSIVE LEACHATES - SALIHOGLU, HULYA (My University, 2016)
Geosynthetic Clay Liners (GCLs) are hydraulic barrier systems in which a thin layer of bentonite (<10 mm) is fixed between two geotextiles by needle punching or glued to a geomembrane. Sodium bentonite (Na-B), the major constituent of GCLs, hydrates upon exposure to liquids such as deionized water and can swell significantly. The corresponding low hydraulic conductivity achieved makes GCLs effective barriers for waste containment systems. However, aggressive characteristics of the hydrating liquid in contact with bentonites in GCLs, such as salinity, cation type, and pH, may alter the bentonite fabric and lead to unacceptable increases in hydraulic conductivity. Polymer-modified bentonites (PMBs) containing a blend of Na-B and various polymers have been introduced in recent years to improve the chemical compatibility and hydraulic performance of GCLs contacted with aggressive leachates. The purpose of this study is to demonstrate that the resistance of PMBs to increases in hydraulic conductivity when contacted with aggressive leachates is maintained over the long term, and to identify potential conditions where this is not the case (e.g., PMB types or permeant solution characteristics). A secondary goal is to improve basic understanding of the physical and chemical mechanisms by which polymer modification leads to improved hydraulic performance. A practical goal of the research is to identify the applicability of conventional index tests (e.g., free swell, fluid loss) and alternative index tests by which the long term hydraulic performance of PMBs may potentially be estimated from more easily determined short-term test procedures. Hydraulic conductivity of GCLs containing natural sodium bentonite (Na-B) and GCLs containing various PMBs (Resistex and Resistex plus) were measured in flexible wall permeameters for specimens permeated with synthetic leachates corresponds to leachates obtained from coal combustion, municipal solid waste combustion (MSW) and heap leach facilities impoundments. Hydraulic conductivity of GCLs were measured for specimens permeated with eight CCP leachates, an MSW incinerator ash (MSW-I) leachate and a gold pregnant leach solution (Gold PLS). Five of the synthetic CCP leachates were selected from CCP leachate database of Electric Power Research Institute (EPRI) representing CCP disposal facilities in the U.S. and referred here as EPRI leachates: typical CCP leachate, predominantly divalent cation ash leachate (low RMD), flue gas desulfurization residual (typical FGD), high ionic strength leachate and trona ash leachate. Chemical characteristics of remaining three CCP leachates (CCP 1, CCP 2 and CCP 3), MSW-I leachate and gold PLS leachate were obtained from coal combustion, municipal solid waste combustion (MSW) and heap leach facilities impoundments around the U.S. and used to produce corresponding synthetic leachates in the laboratory. These leachates were referred here as site-specific leachates. Hydraulic conductivity results are presented for tests that have reached both hydraulic and chemical equilibrium, and for on-going tests where equilibrium has not yet been reached but can be reasonably approximated. Hydration characteristics of Na-B and PMBs in various aggressive solutions and correlations to steady state hydraulic conductivity for GCLs permeated with these solutions are evaluated using conventional (swell index, fluid loss) and an alternative fall cone index test and loss on ignition test. Hydraulic conductivity test results for Na-B GCL with site-specific leachates varied from 9.61 x 10-7 m/s to 2.2 x 10-11 m/s. Four orders of magnitude increase in hydraulic conductivity for Na-B GCL permeated with the site-specific leachates wasobserved as the ionic strength of the leachate increased by a factor of 100. Hydraulic conductivity values for GCLs containing PMB permeated with the site-specific leachates were variable, and ranged from 10-12 to 10-8 m/s. The highest hydraulic conductivity value for these tests (2.27 x 10-8 m/s) was obtained with permeant solution MSW-I (the highest ionic strength leachate, I=1042 mM). Each test with PMB GCLs displayed lower hydraulic conductivity to the site-specific leachates than tests with conventional Na-B GCL. Permeation of PMB GCLs with EPRI leachates resulted in very low hydraulic conductivity values, and within the same order of magnitude (10-12 m/s), regardless of the ionic strength of leachate. PMB GCLs having higher polymer loading had lower hydraulic conductivity to both EPRI leachates and site-specific leachates in all but one case. The long term hydraulic conductivity of Na-B GCL to the EPRI leachates and site-specific leachates was inversely related to swell index (ASTM D5890-11) and directly related to fluid loss (ASTM D5891-02). For the PMB materials, however, no systematic correlation between hydraulic conductivity and either conventional swell index or fluid loss was observed. Liquid limit values extrapolated from laboratory fall cone tests (BS 1377-part 2) was found to be inversely related to hydraulic conductivity of one type of PMB GCL (old generation Resistex) and Na-B GCL to EPRI leachates. No systematic correlation was observed between hydraulic conductivity of other PMB GCLs (Resistex and Resistex plus) and liquid limit obtained from fall cone test. Loss on ignition (LOI) values before any permeation was inversely related to hydraulic conductivity of PMB GCLs having various polymer loading with trona leachate. For the PMB GCLs used in this study, an increase in LOI from 3.15 % to 6.17 % resulted in decrease in hydraulic conductivity to trona leachate by a factor of two. For the other PMB GCLs permeated with trona leachate, increasing polymer loading from 4.0 % to 6.5 %, hydraulic conductivity decreased by 2 order of magnitude (from 8.67 x 10-10 m/s to 4.82 x 10-12 m/s).
Keywords: aggressive leachates; polymer-modified bentonite